The effectiveness of using effective microorganism (EM) for wastewater treatment in residential and industrial area / Umi Fathiah Rusli - Rusli, Umi Fathiah (Faculty of Architecture, Planning and Surveying, 2015)
Wastewater treatment can be done in many ways. Wastewater treatment purposes are to avoid water pollution, kill the organisms in the water especially those can be high potential to bring diseases, and also disappearing uneasy odour and colour in water. In our case, Effective Microorganisms (EM) are being used. Effective microorganism (EM) contains microorganisms like lactic acid bacteria, yeast and photosynthetic bacteria. EM had been through research and development process before I decided to test it in wastewater sample. Locations of case study are at PKNS Flat, Section 7, Shah Alam and HL Rubber, Kuala Pilah. The benefit of using EM rather than other method of wastewater treatment is EM more environmental friendly. By using EM the wastewater which is contaminated can be clean in short period of time but the impact can last for a long term with less finance will be spent. Other than that, this method easily can be done without a lot of equipment or tools will be used. The usage of EM can be used widely in order to achieve towards sustainable environment. In this research, I collected wastewater sample from the both places to work on a few laboratory test. The parameters involved are suspended solid, biochemical oxygen demand, ammonia nitrogen, chemical oxygen demand, turbidity, dissolve oxygen, temperature and the pH value of the wastewater sample. I decided to used residential and industrial wastewater sample and test it at Environmental Lab at Faculty of Civil Engineering, UiTM Shah Alam. 1 ml of Effective Micro activated solution was added into the wastewater sample and stirred it. The most effective reaction given by the EM was at the 7th day because the reaction remained stable till the end. The main objective of this case research was to determine the effectiveness of using EM in improving wastewater quality in drainage system and secondly to identify the classification of wastewater quality between residential and industrial area. At the end of the test, it shows that EM is able to increase the quality of wastewater and suggested to use it as wastewater treatment. The main objectives are successfully achieved.